Penerapan Media Pembelajaran Berbasis Web “Genially” Terhadap Hasil Belajar Siswa Pada Materi Mufradāt Bahasa Arab - Nurjamilah, Siti; Fahyuni, Eni Fariyatul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This research is motivated by Arabic language learning on mufrodat material with the teaching process in class still using conventional methods, lecture methods, and sometimes assisted with powepoint media. However, the media is considered less diverse and innovative so that it still does not attract the attention of students. So that students still have difficulty in learning this mufrodat, because it feels monotonous. Therefore, researchers try to implement Genially web-based learning media on Arabic mufrodat material which has different characteristics from other media because of its interesting gamification features and can give a pleasant impression during the learning process. The purpose of this study is to see the effectiveness and comparison of student learning outcomes before and after the application of genially web-based learning media on mufordat material. This research uses quantitative research with experimental methods with Independent Sample T-Test data analysis, the samples taken in this study were class VIII A as an experimental class with a total of 24 students and class VIII B as a control class with a total of 21 students. The results of this study indicate that the value of a Sig. (2-tailed) 0.003 is smaller than 0.05, which means that there is an influence and significant average difference between learning outcomes with the application of Genially web learning media and those that do not use Genially web application at SMP Muhammadiyah 5 Tulangan.